Using administrative data to examine mental health service use among post-secondary students in Alberta, Canada - Lamba, Navjot; Jagodzinski, Robert (International Journal of Population Data Science, 2018)
Introduction Poor mental health among post-secondary students has been on the rise, and as such, has become a growing concern for the Alberta government. Alberta’s major post-secondary institutions have emphasized the need for evidence that would improve mental health supports for students troubled by mental health issues. Objectives and Approach Responding to the need for evidence, the Child and Youth Data Laboratory profiled the socio-demographic characteristics (sex, socio-economic status, etc) of students who used mental health services between 2005/06 and 2010/11. In addition, using linked administrative data from a range of government programs, the profiles provide new data on the program involvement of post-secondary students who used mental health services, including educational achievement in high school, high cost health service use, the presence of chronic conditions, injury diagnoses, disability status, justice system involvement, income support, and type of mental health condition. Results Over the study period, 7% (~6,000) of post-secondary students received mental health services. Of those, between 11 and 13% were high cost health service users, ~20% received an injury diagnosis, and ~15% had a chronic condition. These proportions were higher compared to the proportions among students who did not receive mental health services. Rates of income support service use, corrections involvement, and students with disabilities were higher compared to students not receiving mental health services. A greater proportion of Canadian students (between 6.5% and 7.1%) compared to non-Canadian students (between 3.4% and 4.1%) received mental health services. In 2010/11, a greater proportion of part-time compared to full-time students were diagnosed with an anxiety disorder (3.4%, part-time; 2.3% full-time) or depression (4.0% part-time; 2.3% full-time). Conclusion/Implications Evidence produced from linked administrative data offers a unique understanding of students who use mental health services, particularly in terms of their government program involvement. This new evidence can be used, for example, to determine if mental health service needs are different for Canadian versus non-Canadian students, or for full-time versus part-time students.